Верховенство права та законність як принципи діяльності Національної поліції - Комзюк, А. Т.; Komziuk, A. T.; Салманова, О. Ю.; Salmanova, O. Y.; Anatolii Komziuk; Olena Salmanova (Правова держава. - 2021. - № 44. - С. 45-53, 2021)
Визначено співвідношення принципів верховенства права і законності та їх значення у діяльності Національної поліції України. Зокрема визначено поняття принципів верховенства права та законності. Принцип верховенства права визначається як ідея панування права, яка втілюється у створення належних законів, їх відповідне виконання, заборону свавілля, дотримання прав людини, недискримінацію та рівність перед законом. Законність розуміється як суворе дотримання, виконання закону. Встановлено співвідношення зазначених принципів, визначено особливості впливу цих принципів на діяльність Національної поліції, обґрунтовано пропозиції щодо удосконалення правового регулювання верховенства права та законності як принципів діяльності Національної поліції України.

The article defines the relationship between the principles of the rule of law and legality and their importance in the activities of the National Police of Ukraine. Indicated, that the principle of the rule of law is enshrined in the Constitution of Ukraine, and in relation to the National Police – also in the Law on it. Attention is drawn to the fact that the definition of the rule of law in the Constitution and the Law of Ukraine «On the National Police» is interpreted differently. Therefore, in a generalized form, the principle of the rule of law is proposed to be interpreted as the idea of the rule of law, which is embodied in the creation of appropriate laws, their proper implementation, prohibition of arbitrariness, human rights, non-discrimination and equality before the law. It was emphasized that it was expedient to define this principle as a general idea in the Law “On the National Police”, as its other components cannot always be fulfilled in the activity of the police. In particular, the authorities and police officers cannot question the compliance of the law with the ideas of social justice, freedom, equality, etc. Nor can they, in the performance of their tasks and functions, be guided by norms of morality, traditions, customs, etc., and not by formally defined norms of law (ie laws). It is in the light of such reservations that it is proposed to define this principle. The police must implement it through certain requirements – legality, prohibition of arbitrariness, respect for human rights, non-discrimination and equality before the law. Therefore, legality is of paramount importance in the activity of the police – the police act exclusively on the basis, within the powers and in the manner determined by the Constitution and laws of Ukraine. In this regard, the proposals to improve the legal regulation of the rule of law and legality as principles of the National Police of Ukraine are substantiated.

Определено соотношение принципов верховенства права и законности и их значение в деятельности Национальной полиции Украины. В частности определено понятие принципов верховенства права и законности. Принцип верховенства права определяется как идея господства права, которая воплощается в создание надлежащих законов, их соответствующее выполнение, запрет произвола, соблюдение прав человека, недискриминации и равенства перед законом. Законность понимается как строгое соблюдение, исполнение закона. Установлено соотношение указанных принципов, определены особенности влияния этих принципов на деятельность Национальной полиции, обоснованы предложения по совершенствованию правового регулирования верховенства права и законности как принципов деятельности Национальной полиции Украины.
Rule of law and legality as principles of National Police activity
Верховенство права и законность как принципы деятельности Национальной полиции
Keywords: Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Національна поліція України. National police of Ukraine. Национальная полиция Украины; National police of Ukraine; Национальная полиция Украины; поліція; police; полиция; правове регулювання; legal regulation; правовое регулирование; верховенство права; rule of law; законність; legality; законность; принципи діяльності поліції; principles of police activity; принципы деятельности полиции